Socialization of Used Cooking Oil Processing into Wax in Pandeyan Village, Ngemplak District, Boyolali Regency: Socialization of Used Cooking Oil Processing into Wax in Pandeyan Village, Ngemplak District, Boyolali Regency - putri, fitria; Putri, Fitria Putri; Meta, Dhea; Hidastri, Ghaliyah; Nurjanah, Alfiah; Premipara, Lensa (Universitas Sahid Surakarta, 2023)
Abstract: One of the causes of environmental pollution is used waste cooking oil. Disposal of used cooking oil can have a negative impact on the environment and human life. We try to provide a solution to overcome this problem by utilizing used cooking oil which can be processed into candles. The community service entitled Socialization of Processing Used Cooking Oil into Candles in Pandeyan Village, Ngemplak District, Boyolali Regency was carried out on Sunday 30 July 2023. The aim is to provide knowledge and skills to the community needed in making candles. The method used is an approach by providing information through counseling regarding the processing of used cooking oil. As a result of this activity, the knowledge and skills of PKK mothers in Garen RT 4/2, Pandeyan Village, Ngemplak District, Boyolali are increasing. Keywords: Waste Cooking Oil, Candle, and Pollution